ANOMALY - A Scientific Exploration of the UFO Phenomenon - Teodorani, Massimo (Journal of Scientific Exploration, 2023)
Book Review – Daniel Coumbe (2023). ANOMALY – A Scientific Exploration of the UFO Phenomenon. Rowman & Littlefield (USA).